1990
DOI: 10.1002/1097-0355(199023)11:3<278::aid-imhj2280110309>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Outcome evaluation in brief mother-infant psychotherapy: A preliminary report

Abstract: The emerging field of mother‐infant psychotherapy lends itself particularly well to objective measures of change. The improvements are often rapid, involving symptom relief or removal. These improvements can be related to subjective change in mothers and to modifications of various interactive variables. We examined changes due to brief therapy (maximum of 10 sessions) in cases of functional and behavioral disturbances in children less than 30 months old. Evaluations were done before treatment and at 1 week, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
11

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(84 citation statements)
references
References 14 publications
2
71
0
11
Order By: Relevance
“…The study population presented similar characteristics to those observed in previous similar studies using a similar therapeutic approach [13,42], in particular a large proportion of sleep disturbances (the most frequent symptom in the present population) and the existence of co-morbidity (presence of behavioral disturbances, functional disturbances and/or emotional difficulties), which was observed in the present study for nearly two-thirds of the children [25,33,39,46]. There was also a large proportion of anxious and, to a lesser extent, depressive symptoms among the mothers [8,22], as well as an association between the mental state of the mother and difficulties experienced by the child (in particular prior to the start of the therapy, and in case of behavioral disorders in the child).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The study population presented similar characteristics to those observed in previous similar studies using a similar therapeutic approach [13,42], in particular a large proportion of sleep disturbances (the most frequent symptom in the present population) and the existence of co-morbidity (presence of behavioral disturbances, functional disturbances and/or emotional difficulties), which was observed in the present study for nearly two-thirds of the children [25,33,39,46]. There was also a large proportion of anxious and, to a lesser extent, depressive symptoms among the mothers [8,22], as well as an association between the mental state of the mother and difficulties experienced by the child (in particular prior to the start of the therapy, and in case of behavioral disorders in the child).…”
Section: Discussionsupporting
confidence: 70%
“…The repercussions of the child's symptoms on the family are also assessed with a score from 1 to 5. The presence of a problem in any given domain was registered if the SCL subscore was greater than 2.5 [threshold chosen in accordance with the results obtained by Cramer et al (1990)]. …”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os estudos descritos por Cramer [41][42][43] avaliaram os efeitos da psicoterapia breve para a melhora dos sintomas do bebê, da qualidade da interação mãe-bebê e da autoestima materna. Seus estudos, realizados na Suíça, consistiram no atendimento de diversas famílias com bebês entre 6 e 30 meses de vida.…”
Section: Psicoterapia Pais-bebê No Contexto Da Depressão Materna: Estunclassified